2018
DOI: 10.5897/ijlp2017.0423
|View full text |Cite
|
Sign up to set email alerts
|

Management and Breeding Objectives of Maefur goat breed type in Erob district eastern Zone of Tigray, Northern Ethiopia

Abstract: A cross sectional survey was conducted to characterize production system and to identify breeding objectives of Maefur goat population in the eastern zone of Tigray, Northern Ethiopia. A pre-tested questionnaire was used for the personal interview with purposively selected 150 households. The data collected through personal household interview were analyzed using descriptive statistics. Indices were used to provide the ranking. The mean (±SD) family size of the household was 8.5±2.1. The average (±SD) livestoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
2
0
1
Order By: Relevance
“…The average mean ages at puberty for males and females were 9.6 and 8.7 months, respectively (Table 6). This is comparable with local goats in Northwestern Amhara (11.1 ± 1.5 months; [8]) and Maefur goats (9.52 ± 0.60 months; [27]). However, it was longer than the age at puberty reported by Abraham et al [4] for Begait goats (7.4 ± 1.9 and 8 ± 1.8 months for males and females, respectively).…”
Section: Reproductive Performancesupporting
confidence: 79%
“…The average mean ages at puberty for males and females were 9.6 and 8.7 months, respectively (Table 6). This is comparable with local goats in Northwestern Amhara (11.1 ± 1.5 months; [8]) and Maefur goats (9.52 ± 0.60 months; [27]). However, it was longer than the age at puberty reported by Abraham et al [4] for Begait goats (7.4 ± 1.9 and 8 ± 1.8 months for males and females, respectively).…”
Section: Reproductive Performancesupporting
confidence: 79%
“…The average mean ages at puberty for males and females were 9.61±0.81 and 8.63±0.90 months, respectively (Table 5). This is comparable with local goats in Northwestern Amhara (11.1 ± 1.5 months; [8]) and Maefur goats (9.52 ± 0.60 months; [22]). However, it was longer than the age at puberty reported by Abraham et al [4] for Begait goats (7.4 ± 1.9 and 8 ± 1.8 months for males and females, respectively).…”
Section: Reproductive Performancesupporting
confidence: 79%
“…Statistically, age of puberty trend seems to increase with decrement of altitude. Current finding is shorter than the report of Weldeyesus and Rohotash (2018) who reported that about 12.7 months for Maefur goat breed managed under traditional management in Erob district, East Tigray. Most of the goats may often reach puberty without having achieved an adequate physical growth to support reproduction and first ovulation may not necessarily coincide with first estrus depending on nutritional status and breed (Greyling, 2010).…”
Section: Reproductive Performance Of Goatcontrasting
confidence: 69%